Foulant Analyses of Ultrafiltration (UF) Membrane Fouled with Natural Organic Matter (NOM) of Ulu Pontian River and Bekok Dam Reservoir - Zularisam, A. W.; Ismail, A. F.; Salim, M. R.; Sakinah, M. (Malaysian Journal of Science, 2008)
An autopsy procedure has been carried out on both clean and fouled polysulfone (PSF) UF membranes with prime intention to investigate the relative effect of NOM fouling onto the membrane characteristics and as well as to identify the primary NOM component that possessed the major fouling potential. A PSF membrane has been fouled with feeds of Bekok Dam reservoir and Ulu Pontian river. Results of foulant analyses showed that the membrane was mainly fouled by the organic NOM fraction of hydrophilic character. In fact, the hydrophilic fraction was found to play a more significant role as the primary foulant that were hypothesized to be responsible for the substantial flux decline during membrane water treatment. Comparatively there were distinctive changes in membrane characteristics from the perspective of contact angle, SEM analysis and membrane zeta potential of NOM fouled membrane, thus adequately supporting the evidence of membrane fouling by the responsible foulant. In particular the membrane wetability and surface charge have been found to decrease significantly after being fouled with both NOM source waters, as a matter of fact the Ulu Pontian river showed greater decrement of membrane properties compared to its counterpart the Bekok Dam reservoir. Thus this observation implied that most of the membrane surface has been covered-up by the non-humic component which could possibly be the primary membrane foulant as it was significantly found to adhere most on the membrane surface. ATR-FTIR analysis revealed that hydrophilic components such as the polysaccharides-like substances, alcoholic compounds and aliphatic amide of protein groups as the responsible materials covering the membrane surface.